The Effect of Work Discipline and Work Environment on Employee Performance Through Work Motivation in the Police Environment - Hidayat, Gagah Maulidin Amirul Mukminin; Renaldi, Hagus (Yayasan Gema Bina Nusantara, 2023)
This study aims to determine the effect of work discipline and work environment on employee performance through work motivation. The population in this study is all employees or staff. Totaling 500 employees, the sample was taken based on random sampling of 145 from various elements of organizational units and positions. The data in this study are divided into two types: primary and secondary. Collecting data using observation, interviews, and the results of distributing questionnaires to employees. Based on the results of the study, it was found that there was no influence of work discipline variables on employee performance processes through work motivation. This means that if H0 is accepted by work discipline, there is no effect on employee performance processes through motivation. There is no effect of work discipline variables on employee performance processes through work motivation. This means that H0 is accepted by work discipline and has no effect on employee performance through work motivation. There is no effect of work environment variables on employee performance through work motivation. This means that if H0 is accepted by the work environment, there is no effect on employee performance through work motivation. There is no effect of work environment variables on employee performance through work motivation. This means that if H0 is accepted by the work environment, there is no effect on employee performance through work motivation.